Complex causality and metacomplexity, elements for building university omniknowledge - Ricardo Pericón Pacheco, Omar (Seven Editora, 2023)
It was possible to identify that university knowledge is not supported by the epistemic, meta-complex and meta-reflexive subject, university teaching is not really related to the requirements of the environment, problems arise when the student concludes their academic training, there are needs, emergencies and uncertainties and they have to face reality. The general objective of the research was to build the concept of ’university omniknowledge’ by linking the elements of complex causality and metacomplexity. The methodology used analytical argumentation, including emergencies, developing complexities, the relevancies considered were: theoretical, methodological, social and transdisciplinary, the method was deductive, explanatory and transdisciplinary, questions, objectives and hypotheses were raised, the research was based on the pragmatism, covered the epistemological and ontological field, exploratory and descriptive studies were carried out, the research design was exploratory transectional and techniques and instruments were used. The research was an original work, obtaining significant information that benefits the individual-society-environment, starting from the educational base, with which it was possible to build university omniknowledge, which is not limiting, specifies useful knowledge, is capable of integrate and allows access to all kinds of knowledge, is practical and is accompanied by experience. DOI: 10.56238/pacfdnsv1-023